Interfacial Chemistry and Catalysis of Inorganic Materials - Tzu-Chin Chang Chien; Murielle F. Delley (CHIMIA, 2024)
Heterogeneous catalysis is essential to most industrial chemical processes. To achieve a better sustainability of these processes we need highly efficient and highly selective catalysts that are based on earth-abundant materials rather than the more conventional noble metals. Here, we discuss the potential of inorganic materials as catalysts for chemical transformations focusing in particular on the promising transition metal phosphides and sulfides. We describe our recent and current efforts to understand the interfacial chemistry of these materials that governs catalysis, and to tune catalytic reactivity by controlled chemical modification of the material surfaces and by use of interfacial electric fields.